A Rare Case Report of Acrania - Arman, DM; Mukherjee, Sudipta Kumer; Ekramullah, Sheikh Muhammad; Uddin, Zia; Rahman, Moshiur (Bangladesh Journal of Neurosurgery, 2022)
Acrania is a rare congenital anomaly and characterized by partial or complete absence of the calvarium. Although acrania associated with anencephaly is a well recognized entity but isolated acrania is a rare anomaly. Ultrasound allows early diagnosis of this anomaly. The fetus was found to have a completely formed brain, base of the skull and facial structures but lacking a cranium. Authors present a rare case of acrania. Bang. J Neurosurgery 2021; 11(1): 50-53